Multiverse theories a philosophical perspective - Friederich, Simon 1988- (Cambridge University Press, 2021)
If the laws of nature are fine-tuned for life, can we infer other universes with different laws? How could we even test such a theory without empirical access to those distant places? Can we believe in the multiverse of the Everett interpretation of quantum theory or in the reality of other possible worlds, as advocated by philosopher David Lewis? At the intersection of physics and philosophy of science, this book outlines the philosophical challenge to theoretical physics in a measured, well-grounded manner. The origin of multiverse theories are explored within the context of the fine-tuning problem and a systematic comparison between the various different multiverse models are included. Cosmologists, high energy physicists, and philosophers including graduate students and researchers will find a systematic exploration of such questions in this important book
Preface; Part I. Setting the Stage: 1. Introduction; 2. The fine-tuning considerations; 3. Fine-tuning for life and design; Part II. Fine-tuning for Life and the Multiverse: 4. The standard fine-tuning argument; 5. Problems with priors; 6. A new fine-tuning argument; Part III. Testing Multiverse Theories: 7. Testing multiverse theories: approach; 8. Approaching practice; 9. Puzzles of self-locating belief; Part IV. Wider Still and Wilder: 10. Other multiverses; 11. Outlook; References; Subject index; Author index
Keywords: bicssc; Wissenschaftsphilosophie; Quantentheorie